Trade union strategies against healthcare marketization : opportunity structures and local-level determinants - Auffenberg, Jennie (London : Routledge, 2021)
Marketization in the healthcare sector affects the quality and delivery of care, as well as healthcare workers' working conditions. Based on a comparison of England and Germany, along with an in-depth case study looking at New York, USA, this volume examines how trade unions respond to marketization processes and the determinants of successful strategies. The author draws on a rich empirical study to develop a theoretical framework that accounts for sector-specific opportunity structures stemming from marketization processes and on the relevant unions' local-level leeway that opens if they build up and mobilise the available resources and capacities. The book identifies determinants of successful trade union strategies, explains the puzzling observation of similar strategic choices across different systems, and draws conclusions for prospects of trade unionism in the marketized healthcare sector. This book emphasizes the transformative effect of marketization on healthcare and the opportunities this change creates for unions, while giving special attention to the local-level conditions of trade unionism in the analysis of conflicts evolving around marketization in the hospital sector. It is of interest to academics and practitioners working in healthcare management, human resource management, and employment relations.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Great Britain -- Marketing; Medical care -- Germany -- Marketing; Medical personnel -- Labor unions -- Great Britain; Medical personnel -- Labor unions -- Germany; Health services administration -- Great Britain; Health services administration -- Germany; BUSINESS & ECONOMICS / Human Resources & Personnel Management; MEDICAL / Administration